2013
DOI: 10.1002/grl.50946
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of Fe3S above 250 GPa

Abstract: We have determined subsolidus phase relations in the Fe–FeS system up to 271 GPa using laser‐heated diamond‐anvil cell techniques. In situ synchrotron X‐ray diffraction (XRD) measurements performed at high pressure and high temperature demonstrate the coexistence of hexagonal close‐packed (hcp) Fe and tetragonal Fe3S up to 241 GPa and 2510 K. In contrast, the XRD data obtained above 250 GPa show that the hcp phase coexists with the CsCl (B2)‐type phase for three different Fe–S bulk compositions (10, 16, and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 36 publications
0
40
2
Order By: Relevance
“…On the other hand, the previous DAC study by Kamada et al (2012) showed that maximum ∼4 wt.% sulfur dissolves into hcp iron at 123 GPa. More recent experiments by Ozawa et al (2013) demonstrated that the hcp phase formed in the Fe-FeS system at 270 GPa, although they reported only the upper bound of sulfur content (7.5 wt.% sulfur) in hcp iron. The effect of sulfur on stable crystal structure remains to be examined experimentally at inner core P-T conditions.…”
Section: Crystal Structure Of Fe-si Alloy In the Inner Corementioning
confidence: 95%
“…On the other hand, the previous DAC study by Kamada et al (2012) showed that maximum ∼4 wt.% sulfur dissolves into hcp iron at 123 GPa. More recent experiments by Ozawa et al (2013) demonstrated that the hcp phase formed in the Fe-FeS system at 270 GPa, although they reported only the upper bound of sulfur content (7.5 wt.% sulfur) in hcp iron. The effect of sulfur on stable crystal structure remains to be examined experimentally at inner core P-T conditions.…”
Section: Crystal Structure Of Fe-si Alloy In the Inner Corementioning
confidence: 95%
“…Based on this observation and the binary eutectic liquid compositions inferred from previous studies (Komabayashi, 2014;Morard et al, 2017;Mori et al, 2017), we estimate the liquidus field of Fe in the Fe-S-O ternary at 330 GPa, which extends to relatively S-poor and O-rich compositions (Figure 3d). Although our experiments were performed below the decomposition pressure of Fe 3 S (Ozawa et al, 2013), it does not cause a discontinuous jump in the eutectic liquid composition and should not change our estimate of the eutectic composition at 330 GPa remarkably (Mori et al, 2017). Badro et al (2014) argued that the outer core is sulfur-poor (0-2 wt% S) and oxygen-rich (4-5.5 wt% O) in order to account for seismological observations of its density and bulk sound velocity when S and O are the core light elements.…”
Section: Constraint From Liquidus Phase Relationsmentioning
confidence: 99%
“…The presence of these light elements explains the density deficit of the core. Although the concentration and the chemical form of the light elements remain open questions, S, Si, and O are the primary candidates for light elements contained in the core [ Chen et al, ; Kamada et al, , ; Ozawa et al, ; Seagle et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…However, high‐temperature experiments [ Sata et al, ] indicate that above 180 GPa, FeS adopts B2 structure under heating. High‐pressure experiments on Fe 3 S [ Ozawa et al, ] indicate that this compound decomposes into FeS‐B2 and Fe‐hcp when compressed to 264 GPa and heated to 2540 K.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation